Pendidikan Kesehatan Keluarga Tentang Diare Pada Balita - Sulistiyowati Sulistiyowati; Vera Febrianti Sukma; Putri Alifia Octaviyana; Faradila Ranantia (Universitas Muhammadiyah Mataram, 2022)
Abstract: Diarrhea is still a major cause of illness and death in almost all of the world with a high incidence occurring mostly in infants and toddlers. The purpose of this community service is to provide health education to families about diarrheal diseases, especially how to prevent and treat diarrhea at the family level. The health education methods provided are lectures and questions and answers as well as the provision of leaflets so that it can facilitate the provision of health education and can be well received by the family which is divided into 4 stages, namely opening, core, question and answer and closing. In health education activities about diarrhea in toddlers, there is a level of understanding in the families of toddlers about diarrhea, especially in the prevention and treatment of diarrhea that is good and correct, and the participants are active and enthusiastic during the question and answer session. Abstrak: Diare masih merupakan penyebab utama kesakitan dan kematian hampir di seluruh dunia dengan kejadian yang tinggi lebih banyak terjadi pada bayi dan balita Tujuan Pengabdian masyarakat ini adalah memberikan pendidikan kesehatan kepada keluarga tentang penyakit diare terutama cara pencegahan dan pengobatan diare di tingkat keluarga. Metode Pendidikan kesehatan yang diberikan adalah ceramah dan tanya jawab serta pemberian leaflet sehingga dapat memudahkan pemberian pendidikan kesehatn dan dapat diterima dengan baik oleh keluarga yang dibagi menjadi 4 tahap yaitu pembukaan, inti, tanya jawab dan penutup. Kegiatan Pendidikan kesehatan tentang diare pada balita terjadi tingkat pemahaman pada keluarga balita tentang diare terutama dalam pencegahan dan pengobatan diare yang baik dan benar terlihat dan keaktifan peserta dan antusias saat sesi tanya jawab.